Interference Mitigation Technique Through Shielding and Antenna Discrimination - Abdulrazak, Lway Faisal; Oudah, Ali A. (SERSC, 2015)
nterference mitigation between IMT-Advanced and Fixed Satellite Services (FSS) is presented in this article. Toward this goal, an analytical model has been developed based on the deterministic analysis of the propagation model. The IMT-Advanced system parameters have been represented by Worldwide Interoperability for Microwave Access (WiMAX) 802.16e. The use of VSAT unit and different shielding materials is considered. The testing is performed in the Anechoic Chamber as well as outdoor, and deployment is designed to fulfill FSS signal receiving criteria. A strong positive correlation was found between path loss parameters various terrains for different deployment areas. The Antenna discrimination has been discussed alongside the shielding absorption coefficients of the suggested materials. Then the antenna discrimination proposal is demonstrated with a high degree of capability to reduce the harmful power interference from IMT-Advanced base station towards the FSS receiver.